Shoulder rotator muscle dynamometry characteristics: Side asymmetry and correlations with ball-throwing speed in adolescent handball players - Pontaga, I.; Zidens, J. (Journal of Human Kinetics, 2014)
The aim of the investigation was to: 1) compare shoulder external/internal rotator muscles` peak torques and average power values and their ratios in the dominant and non-dominant arm; 2) determine correlations between shoulder rotator muscles` peak torques, average power and ball-throwing speed in handball players. Fourteen 14 to 15- year-old male athletes with injury-free shoulders participated in the study (body height: 176 ± 7 cm, body mass 63 ± 9 kg). The tests were carried out by an isokinetic dynamometer system in the shoulder internal and external rotation movements at angular velocities of 60°/s, 90°/s and 240°/s during concentric contractions. The eccentric external- concentric internal rotator muscle contractions were performed at the velocity of 90°/s. The player threw a ball at maximal speed keeping both feet on the floor. The speed was recorded with reflected light rays. Training in handball does not cause significant side asymmetry in shoulder external/internal rotator muscle peak torques or the average power ratio. Positive correlations between isokinetic characteristics of the shoulder internal and external rotator muscles and ball-throwing speed were determined. The power produced by internal rotator muscles during concentric contractions after eccentric contractions of external rotator muscles was significantly greater in the dominant than in the non-dominant arm. Thus, it may be concluded that the shoulder eccentric external/concentric internal rotator muscle power ratio is significantly greater than this ratio in the concentric contractions of these muscles